Pemanfaatan Limbah Sagu Menjadi Biochar bagi Masyarakat di Negeri Seruawan, Seram Bagian Barat - Laury Marcia Ch. Huwae; Ronald D. Hukubun; Rina S. D. Suganda; Suranti Pratiwi; Gresti Vionae; Yulius Ruspanah; M. Aldi Septian; Megumi I. P. Malle; Michele C. Manuputty; Labibah Nur Dini; Aidah Z. N. Rohmah; Aldi Renata (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Sago waste is a significant environmental problem in sago-producing areas, including Seruawan Village. This waste is often burned or simply dumped, which has the potential to cause environmental pollution and reduce soil quality. Therefore, the utilization of sago waste into biochar can be a sustainable and environmentally friendly solution. Biochar is a carbon product resulting from the pyrolysis process of organic matter, which can improve soil fertility and reduce greenhouse gas emissions. By utilizing sago waste into biochar, the community in Seruawan Village can not only reduce waste, but also increase their agricultural productivity. The methodology used is through observation, interviews, technology utilization, and participatory action research. Through a systematic and participatory methodology, this service is expected to make a significant contribution to the management of sago waste into biochar, and improve the welfare of the community in Seruawan Village.